Analysis of Toll-like Receptor 9 Gene Polymorphisms in Sepsis - (:unkn) unknown (INT INST ANTICANCER RESEARCH, 2016)
Aim: To analyze the effect of TLR-9 (-1486 T>C) and TLR-9 (C>T) gene polymorphisms both at TLR-9 levels and together with their sepsis parameters. In this regard, the polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique was used in order to detect TLR-9 gene polymorphisms, whereas the ELISA technique was used to analyze TLR-9 serum levels in 80 sepsis patients and 100 healthy individuals. Materials and Methods: The study group consisted of 80 patients with a diagnosis of sepsis and 100 healthy individuals. TLR-9 C>T polymorphism was identified by PCR-RFLP. Results: There was no substantial difference observed between sepsis and control groups in terms of TLR-9 (-1486 T>C) and TLR-9 (C>T) genotype and allele distribution. When serum TLR-9 levels were compared to TLR-9 (-1486 T>C) and TLR-9 (C>T) genotype and allele distribution, there was a statistically substantial decrease in TLR-9 serum levels of both TLR-9 (-1486 T>C) TT and TLR-9 (C>T) TT individuals in the sepsis group (p=0.011 and p=0.036, respectively). Conclusion: There is no relation between sepsis and both TLR-9 (C>T) and TLR-9(-1486 T>C) polymorphisms; however, there is a relation between sepsis and decreased serum TLR-9 levels of both TLR-9 (-1486 T>C) TT and TLR-9 (C>T) TT polymorphisms due to sepsis-associated immunosuppression.
Keywords: Toll-like receptors; sepsis; polymorphism; inflammation; SURVIVING SEPSIS; SEPTIC SHOCK; GUIDELINES; MUTATIONS; RESPONSES; OUTCOMES; SIGNALS; RISK